Morphology of the Aesthetic Design of the Spherical Shape in Contemporary Ceramic Works - Al-Atoom, Yacoub; Khasawneh, Fuad (Dirasat: Human and Social Sciences, 2021)
This study aims to explore the aesthetics of design in ceramics through spherical formations, and researching the secrets of the morphology of the formalism and structural of ceramic works and their aesthetic and visual impact, and the relationship of circular shapes in building the aesthetic design of the spherical shape in contemporary ceramic artwork. Where researchers used the descriptive analytical approach to suit the nature of the research, and a description and analyzed some contemporary ceramic designs, in terms of the method of construction, aesthetic values, technique, and the method of their production, for a group of Arab potters. In light of the foregoing, the researcher reached a set of results, the most important of which are artists using expressive and symbolic connotations of spherical shapes, aesthetic blending between the geometric and spherical shape of ceramic designs, and the use of Arabic calligraphy in the spherical model as a decorative element, and a morphology distinct from the formalism and structural aspect and consistent with the general idea of the shape.